2003
DOI: 10.1016/s1607-551x(09)70509-1
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone‐Induced Agranulocytosis: A Case Report

Abstract: A 43-year-old woman with liver cirrhosis and hepatocellular carcinoma was admitted for the chief problem of ascites. Laboratory data revealed a leukocyte count of 3.8 x 10(9)/L on the second day of admission. Spironolactone was prescribed for diuresis beginning on the third day. Routine blood tests on the tenth day disclosed marked leukopenia (1.8 x 10(9)/L). Four days later, the leukocyte count was still 1.8 x 10(9)/L and a differential count revealed agranulocytosis (neutrophils, 0.25 x 10(9)/L). Eight days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Case reports have demonstrated that spironolactone can cause agranulocytosis [ 1 , 2 , 3 ]. Advanced age, hepatic and renal impairment and concurrent medications have all been identified as contributing to the likelihood of this adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have demonstrated that spironolactone can cause agranulocytosis [ 1 , 2 , 3 ]. Advanced age, hepatic and renal impairment and concurrent medications have all been identified as contributing to the likelihood of this adverse effect.…”
Section: Discussionmentioning
confidence: 99%